Leak Detection in MDPE Gas Pipeline using Dual-Tree Complex Wavelet Transform - N. F., Adnan; M. F., Ghazali; Makeen, Mohd Amin; Abdul, Malik; Akmal, Ariffin (AENSI Publishing, 2014)
The pipeline system plays the important role in the industry and commonly use as media transport in the piping field on the land or on the sea as well. They are buried underground or situated in the wall of the buildings. The maintenance should be done properly to avoid any leakage to the surrounding. Therefore, the detection of the leak detection is the main investigation issue in order to get the fast and reliable leak detection method. Even though the reasons for these leaks are very well known, some of the current method is quite complicated and not precise. In addition, it is all about time consuming and cost of installment. In this paper, we proposed a leak detection method using acoustic. The chirp signal injected into the pipeline system and the estimation of the leak location from the delay time passing by the reflection in the pipeline if there have a leak. Using Dual Tree Complex Wavelet Transform, the signal filtered and decomposed into five levels. Then, the cepstrum analysis was used to detect the echoes for leak location estimation. When a leak occurred, the new peak shows and identified the presence in the pipeline network. The leak detected at a certain point and the error in this experiment is 0.62 % for leak location and 1.24 % for the outlet., which is nearly accurate to the original leak position. The DTCWT and ceptrum analysis could give acceptable result and possible to identify leaks that are difficult to find by other method.